Prevalence of cattle ticks in various agro-ecological zones of Khyber Pakhtunkhwa, and evaluation of botanical extracts against Hyalomma detritum - Khalid Muhammad; Atif Idrees; Jamshaid Iqbal; Usman Arif; Muhammad Safdar Baloch; Muhammad Faisal Shahzad; Islem Abid; Mohamed Ragab AbdelGawwad (Journal of King Saud University: Science, 2023)
Background: The occurrence of infestation by ticks on livestock is a significant challenge in several semi-tropical and tropical countries including Pakistan. Polluted environment and adapted tolerance by ticks against acaricide are the limiting factors that restrict the management of ticks globally. Methods: In this study, we evaluated the infestation by ticks on cattle from numerous livestock farms present in different districts and agroecological areas of Khyber Pakhtunkhwa, a province in Pakistan. Furthermore, we compared the anti-tick efficacy of different botanicals using ethanolic and aqueous extracts to control Hyalomma detritum. Results: The prevalence rate was 1.78, 35.37, 36.23, 8.15, 15.50, 0.29 and 2.67 percent for Amblyoma varigatum (A. varigatum), Hyalomma anatolicum (H. anatolicum), H. detritum, Hylomma rufipes (H. rufipes), Hyalomma truncatem (H. truncatum), Rhipicephalus microplus (R. microplus), and Hyalomma kashmirensis (H. kashmirensis), respectively. In terms of high mortality rate of ticks, extracts derived from Calotropis procera flower (93.33%), Citrullus colocynthis fruit (95.0%) and Calotropis procera flower (89.4%) showed significantly high efficancy (P < 0.05) than the extracts derived from other plants. In terms of their efficacy in causing mortality of H. detritum tick, Calotropis procera flower, Citrullus colocynthis fruit and Calotropis procera leaves extracts displayed non-significant variation. Conclusion: This work revealed that the cattle tick H. detritum can be successfully controlled by employing both ethanolic and aqueous plant extracts. The intensive use of insecticides and chemical drugs are costly and may affect human health negatively due to residual effects in milk and animal meat.